Curing Techniques of Composite Resin: Continuous or Intermittent? - Niha Naveed1 , Kishorekumar S2 (Institute of Medico-legal Publications Pvt Ltd, 2020)
While composites have continued to be refined, significant differences between the available systems inphysical and mechanical properties, and clinical performance have minimized. Nevertheless, with all thechanges, there is one constant: it is necessary to light-cure direct composites. Clinicians need to understandthe importance of light curing principles because unbound monomers are cytotoxic and poorly curedcomposites are less biocompatible. Four techniques are currently available for light-curing composites.The clinician will consider multiple factors once the light source is chosen to ensure that the composite issatisfactorily cured. This article analyses the various current technologies, their strengths and weaknesses,and the importance to ensuring proper polymerization by following such protocols.